Pregunta
upstudy study bank question image url

27. \( \frac{15^{7} \times 8^{6}}{5^{6} \times 24} \) 28. \( \frac{2^{2005} \times 5^{2000}}{100^{1000}} \) 29. \( \frac{7^{2 x}-1}{3 \times 7^{x}+3} \) 30. \( \frac{16^{x}-1}{5 \times 4^{x}-5} \) 31. \( \frac{25^{x}-4}{2 \times 5^{x}-4} \) 32. \( \frac{9^{x}-3^{x}-2}{6^{x}-2^{x+1}} \)

Ask by Marsh Weber. in South Africa
Feb 26,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

27. \( 3^6 \times 5 \times 2^{15} \) 28. 32 29. \( \frac{7^x - 1}{3} \) 30. \( \frac{4^x + 1}{5} \) 31. \( \frac{5^x + 2}{2} \) 32. \( \frac{3^x + 1}{2^x} \)

Solución

Below are the step‐by‐step simplifications: 27. Simplify (15⁷ × 8⁶)/(5⁶ × 24).  • Write 15 and 8 as products of primes:   – 15 = 3·5, so 15⁷ = 3⁷ × 5⁷.   – 8 = 2³, so 8⁶ = (2³)⁶ = 2¹⁸.  • Factor the denominator:   – 24 = 3 × 8 = 3 × 2³, so 5⁶ × 24 = 5⁶ × 3 × 2³.  • Thus,    (15⁷ × 8⁶)/(5⁶ × 24) = (3⁷ × 5⁷ × 2¹⁸)/(5⁶ × 3 × 2³)  • Cancel common factors:   – For 3: 3⁷/3 = 3⁶.   – For 5: 5⁷/5⁶ = 5.   – For 2: 2¹⁸/2³ = 2¹⁵.  • The simplified expression is 3⁶ × 5 × 2¹⁵. 28. Simplify (2^2005 × 5^2000)/(100^1000).  • Rewrite 100 as 10². Then 100^1000 = (10²)^1000 = 10²⁰⁰0.  • Since 10 = 2×5, we have 10²⁰⁰0 = 2²⁰⁰0 × 5²⁰⁰0.  • Now,   (2^2005 × 5^2000)/(2^2000 × 5^2000) = 2^(2005–2000)= 2⁵ = 32. 29. Simplify (7^(2x) – 1)/(3×7^x + 3).  • Notice the numerator is a difference of squares: 7^(2x) – 1 = (7^x – 1)(7^x + 1).  • Factor the denominator: 3×7^x + 3 = 3(7^x + 1).  • Cancel the common factor (7^x + 1) (assuming 7^x ≠ –1):   Result = (7^x – 1)/3. 30. Simplify (16^x – 1)/(5×4^x – 5).  • Write 16^x in terms of 4^x: 16^x = (4²)^x = 4^(2x). Then numerator = 4^(2x) – 1.  • Recognize the difference of squares: 4^(2x) – 1 = (4^x – 1)(4^x + 1).  • Factor the denominator: 5×4^x – 5 = 5(4^x – 1).  • Cancel (4^x – 1) (provided 4^x ≠ 1):   Result = (4^x + 1)/5. 31. Simplify (25^x – 4)/(2×5^x – 4).  • Write 25^x as (5²)^x = 5^(2x). So numerator = 5^(2x) – 4.  • Notice that 5^(2x) – 4 is a difference of squares: 5^(2x) – 4 = (5^x)² – 2² = (5^x – 2)(5^x + 2).  • Factor the denominator: 2×5^x – 4 = 2(5^x – 2).  • Cancel the common factor (5^x – 2) (assuming 5^x ≠ 2):   Result = (5^x + 2)/2. 32. Simplify (9^x – 3^x – 2)/(6^x – 2^(x+1)).  • Express all terms in prime bases:   – 9^x = (3²)^x = 3^(2x).   – 6^x = (2×3)^x = 2^x×3^x.   – 2^(x+1) = 2×2^x.  • Rewrite the numerator with t = 3^x:   – Numerator becomes t² – t – 2, which factors as (t – 2)(t + 1); that is, (3^x – 2)(3^x + 1).  • Rewrite the denominator:   – Denom = 2^x×3^x – 2×2^x = 2^x(3^x – 2).  • Cancel (3^x – 2) (assuming 3^x ≠ 2):   Result = (3^x + 1)/(2^x). These are the simplified forms for problems 27–32.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Beyond the Answer

The problems you’ve presented are great for illustrating how exponents, factoring, and simplification can be applied in mathematics. For instance, with expressions like \(\frac{15^{7} \times 8^{6}}{5^{6} \times 24}\), one can simplify first by breaking down the components into their prime factors for easier calculation—a nifty skill to save time and frustration! As for real-world applications, understanding these expressions often comes in handy in fields such as finance and science. For instance, when calculating compound interest, the use of exponentiation comes into play. Similarly, physics equations often use exponents to describe exponential decay or growth, so mastering these problems translates directly into skills useful in everyday problem-solving scenarios!

preguntas relacionadas

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Álgebra Mexico Feb 26, 2025
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad